Study the adsorption properties of magnetite nanoparticles in the presence of different synthesized surfactants for heavy metal ions removal - Fawzia I. El-Dib; Dalia E. Mohamed; Omnia A.A. El-Shamy; Marwa R. Mishrif (Egyptian Journal of Petroleum)
Co-precipitation method is used to prepare magnetite nanoparticles (Fe3O4) which stabilized by two nonionic and one cationic surfactant. 1H NMR used to confirm the chemical structure of the synthesized surfactants. The prepared magnetite nanoparticles characterized by size distribution (DLS), Fourier transform infrared spectroscopy (FTIR), and magnetic properties (magnetic susceptibility analysis). X-ray diffraction (XRD) illustrated a cubic crystalline structure of the prepared magnetite nanoparticles. Transmission electron microscope (TEM) images showed that the magnetite nanoparticles had uniformly dispersed. The adsorption efficiency of the prepared nanoparticles toward lead, zinc, and cadmium, metal ions was estimated by using atomic absorption spectroscopy (AAS). There are several factors controlling the uptake enhancement studies of the synthesized nanoparticles such as the pH of the metal ion solutions and adsorbent doses. Keywords: Magnetite nanoparticles, Co-precipitation, Cationic surfactants, Nonionic surfactants, Heavy metals removal